Optimal design of control systems Stochastic and deterministic problems - Kolosov, G. E. (Monographs and textbooks in pure and applied mathematics, 1999)
This groundbreaking reference/text covers design methods for optimal (or quasioptimal) control algorithms in the form of synthesis for deterministic and stochastic dynamical systems--with applications to biological, radio engineering, mechanical, and servomechanical technologies